2001
DOI: 10.1046/j.1365-2249.2001.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for the Th2 predominance in patients with chronic hepatitis C

Abstract: SUMMARYA T helper (Th)1 to Th2 shift has been proposed to be a critical pathogenic determinant in chronic hepatitis C. Here, we evaluated mitogen-induced and hepatitis C virus (HCV) core antigen-induced cytokine production in 28 patients with biopsy-proven chronic hepatitis C. Flow cytometry demonstrated that after mitogenic stimulation the percentage of Th2 cells (IL-4 1 or IL-13 1) and Th0 cells (IFN-g/ IL-4 1 or IL-2/IL-13 1) did not differ between patients and controls. In contrast, the percentage of Th1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…Regarding cytokine responses to persistent HCV infection, past reports in diversified patient groups were rather inconsistent: enhanced T H 1 responses [26 -29], T H 2 responses [30 -32], or both types [33,34]. Although differing degrees of pathogenesis and/or inflammation among study patient groups may be in part responsible for this discrepancy [34,35], some potential methodological drawbacks in studies demonstrating T H 2 cytokine predominance were indicated [27]. The present study on lymphocyte subsets suggested enhanced T H 1 immunity in persistent HCV infection, supporting a view that enhanced T H 1 immunity alone is not sufficient to regulate the virus in many cases of HCV infection.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding cytokine responses to persistent HCV infection, past reports in diversified patient groups were rather inconsistent: enhanced T H 1 responses [26 -29], T H 2 responses [30 -32], or both types [33,34]. Although differing degrees of pathogenesis and/or inflammation among study patient groups may be in part responsible for this discrepancy [34,35], some potential methodological drawbacks in studies demonstrating T H 2 cytokine predominance were indicated [27]. The present study on lymphocyte subsets suggested enhanced T H 1 immunity in persistent HCV infection, supporting a view that enhanced T H 1 immunity alone is not sufficient to regulate the virus in many cases of HCV infection.…”
Section: Discussionmentioning
confidence: 93%
“…Although the dominance of Th2 cytokines in HCV patients is not sufficient for the establishment of chronic infection, 78,79 the development of chronic HCV infection has been linked to a weak or absent Th1 response and the presence of Th2 cytokines. 31,32,34,35,80,81 In addition, clearance of chronic HCV infection upon IFN-␣ treatment is associated with a shift from a Th2-dominant to a Th1-dominant phenotype.…”
Section: Therapeutically Relevant Concentrations Of Ifns Differentialmentioning
confidence: 99%
“…Thus in addition, data suggest that a dysregulation exists in the peripheral CD4 + T‐cell population such that inappropriate cytokines are made in response to viral antigens accounting for viral persistence and evolution of chronic disease. However, the results of the different studies are conflicting in respect to the predominating TH1 or TH2 cytokine response resulting in the inability of the host to terminate HCV infection [12–23].…”
Section: Introductionmentioning
confidence: 99%